Impact pathways of a participatory local governance initiative in Uganda: A qualitative exploration - Van Campenhout, Bjorn; Bizimungu, Emmanuel; Smart, Jenny; Kabunga, Nassul S. (International Food Policy Research Institute, 2017)
The baraza project, initiated in 2009, is a government-led initiative in Uganda that aims to increase the quality of public service delivery through the provision of information and the involvement of beneficiaries in project monitoring by means of providing citizens with an advocacy forum. This study provides a qualitative assessment of the self-identified pathways through which barazas are expected to influence public service delivery, as expressed by participant stakeholders; and the motivating factors behind behavioral changes surrounding the baraza implementation, hindrances to achieving positive outcomes, and opportunities in the implementation of barazas in the future.